Transforming Teen Communication Through the Visual Influence of Social Media - Agustin, Selly; Hafidloh, Nurul; Damayanti, Lutfia Putri; Abadi , Totok Wahyu (Indonesian Journal of Cultural and Community Development, 2024)
General Background: Social media has become a significant platform for adolescents to express themselves and interact with others. The rise of visual-based communication through platforms such as Instagram has shifted traditional communication patterns, moving beyond text-based messaging to photo and video sharing. Specific Background: The rapid increase in social media use among teenagers presents an opportunity to study how these platforms influence communication patterns. While previous studies have explored social media impacts, there is a lack of comprehensive analysis focusing on the evolving nature of communication through visual content. Knowledge Gap: Although numerous studies have analyzed social media use, few have used bibliometric methods to systematically map the trends in adolescent communication patterns across various platforms. The role of visual communication through social media in reshaping teenage interaction patterns remains underexplored. Aims: This study aims to observe how social media use, particularly Instagram, has influenced adolescent communication patterns by employing bibliometric methods through VOSviewer software. Results: The bibliometric analysis identified a shift in adolescent communication patterns, with a growing emphasis on visual content like photos and videos rather than text-based communication. The data showed seven keyword clusters, mostly interconnected, with Instagram, communication, and adolescent communication being the most prominent topics in 2021, with 109 articles. Novelty: This research introduces a novel approach by applying bibliometric methods to analyze and visualize the impact of social media on teenage communication patterns, providing a clearer understanding of how communication has evolved in the digital age. Implications: The findings suggest that social media platforms are reshaping how teenagers communicate, with significant implications for future communication research and the development of digital communication strategies targeting adolescents. The use of bibliometric tools like VOSviewer enables researchers to map research trends effectively, offering new insights into social media’s role in modern communication patterns. Highlights: Social media promotes visual communication among adolescents, shifting from text. Bibliometric analysis identifies seven key clusters in Instagram-related research. VOSviewer effectively visualizes trends in teenage communication patterns. Keywords: social media, Instagram, teenage communication, bibliometric analysis, VOSviewer